DETERMINANTS OF THE PROFITABILITY OF BANK PEMBANGUNAN DAERAH IN SULAWESI - Mustopa, Medi; Muslimin, Muslimin; Kadang, Juliana (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2021)
This research aims to analyze the determinants of credit risk factors, operational risk, liquidity risk, market risk, governance (GCG), earning, capital, bank size, and core capital that have a partial or simultaneous influence on the profitability of Bank Pembangunan Daerah (BPD) in Sulawesi for the 2016-2020 period using the risk-based bank rating (RBBR) method with a quantitative descriptive approach. Data collection used an annual financial report published through each bank at 4 (four) regional banks headquartered in Sulawesi. The factors tested are credit risk with NPL (Non-Performing Loan) proxy, an operational risk with BOPO proxy (Operational Income Operating Expenses ratio), liquidity risk with LDR (Loan to Deposit Ratio) proxy, a market risk with PDN ratio proxy (Position Net Foreign Exchange), governance (GCG), profitability with NIM (Net Interest Margin) proxy, capital with CAR (Capital Adequacy Ratio) proxy, bank size as proxy for total assets, core capital ratio (MI) and profitability with profitability return proxies on assets (ROA). Based on the results of the Simultaneous F test research, shows that credit risk, operational risk, liquidity risk, market risk, governance (GCG), profitability, capital, bank size, and core capital simultaneously have a significant influence on profitability for the 2016-2020 period with the profitability value of F-statistic is smaller than alpha (0.05) which is 0.0000 <0.05. The results of the Partial T-test show that there are 6 (six) factors, each of which has a partial influence on ROA profitability, namely NPL, BOPO, LDR, NIM, CAR, and total assets with a probability value of t-statistic smaller than alpha (0.05 ) that is equal to 0.0000 <0.05 and 3 (three) factors, each of which has no partial influence on ROA profitability, namely governance (GCG), PDN and MI probability value of t-statistic is greater than alpha (0.05 ) that is equal to 0.0000 > 0.05. Keywords: Risk Profile, Good Corporate Governance, Earning, Capital, and Risk-Based Bank Rating (RBBR)